Utility of oxcarbazepine in the treatment of childhood and adolescent psychiatric symptoms. Issue 1 (2nd January 2021) - Morrow, Kyle; Young, Keith A.; Spencer, Shawn; Medina, Edgar Samuel; Marziale, Michaela A.; Sanchez, Alejandro; Bourgeois, James A.
Abstract: The primary aims of this study were to determine if oxcarbazepine is a safely tolerated option for treatment of psychiatric symptoms in children and whether its use facilitates dose modification of other psychotropic medications. A retrospective chart review was completed using data extracted from the electronic medical record of a large outpatient child psychiatry clinic. A total of 507 of 740 children prescribed oxcarbazepine for psychiatric indications for 3 months or more had adequate data to assess clinical responses and medication outcomes. Most patients prescribed oxcarbazepine experienced clinically significant control of irritability/anger, mood stabilization, aggressive outbursts, impulsivity, or anxiety, with over 80% achieving at least maintenance symptom control. In all, 51% and 25% fully discontinued second- or third-generation antipsychotic or antidepressant medication, respectively, after starting oxcarbazepine; 8% discontinued oxcarbazepine for nonresponse, while 9% stopped oxcarbazepine because of emergent side effects. In patients fully discontinuing or reducing the second- or third-generation antipsychotic dose by 50% or more, improvements in body mass index were observed. Oxcarbazepine may prove to be an appropriate alternative to antipsychotic and antidepressant medications for treating psychiatric symptoms in children and adolescents. In particular, it may be a more metabolically neutral psychotropic medication.